Moby-Dick; or, The Whale - Melville, Herman, 1819-1891 (Salt Lake City, UT : Project Gutenberg, 1991)
"Moby-Dick; or, The Whale" by Herman Melville is an epic novel published in 1851. Sailor Ishmael narrates the obsessive quest of Captain Ahab, who commands the whaling ship Pequod in pursuit of Moby Dick, the white whale that destroyed his leg. Driven by vengeance, Ahab leads his diverse crew across the world's oceans, hunting the legendary creature. This tale of obsession explores themes of good and evil, fate, and humanity's struggle against nature's overwhelming power. (This is an automatically generated summary.)
Project Gutenberg eBook #15 is believed to have the highest quality of the three editions of this eBook in the Project Gutenberg collection, and is based on the 1st American edition, 1851. #2701 and #2489 are the others. In addition, there is a computer-generated audio eBook, #9147, and a human audio performance, #28794.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Moby-Dick
Release date is 1991-05-01
Eugene F. Irey
Keywords: Whaling -- Fiction; Sea stories; Psychological fiction; Ship captains -- Fiction; Adventure stories; Mentally ill -- Fiction; Ahab, Captain (Fictitious character) -- Fiction; Whales -- Fiction; Whaling ships -- Fiction